Bolečina ob rojstvu otroka in spomin nanjo - Pondelek, Damjana (Monitor ISH, 2005)
Childbirth pain and its memory. The paper presents an analysis of the stories submitted to the magazine Ona (She) for the competition Her Story - Birth, with an emphasis on the theme of motherhood. The stories and recollections of giving birth are reconstructed from the scraps of memory and stories which linger after the ritual performance of giving birth. The pain recollected by the individual many years later is not only a part of her own childbirth experience, but also a fusion of her memory and desire, of the historical and the imaginary body. These pages reveal Her Story of giving birth and suffering, a story that often remains unspoken.
Keywords: human pregnancy; nosečnost; rojstvo; rojevanje; bolečina; woman; ženske; ideologija